2015
DOI: 10.1371/journal.ppat.1004863
|View full text |Cite
|
Sign up to set email alerts
|

IFIT1 Differentially Interferes with Translation and Replication of Alphavirus Genomes and Promotes Induction of Type I Interferon

Abstract: Alphaviruses are a group of widely distributed human and animal pathogens. It is well established that their replication is sensitive to type I IFN treatment, but the mechanism of IFN inhibitory function remains poorly understood. Using a new experimental system, we demonstrate that in the presence of IFN-β, activation of interferon-stimulated genes (ISGs) does not interfere with either attachment of alphavirus virions to the cells, or their entry and nucleocapsid disassembly. However, it strongly affects tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(108 citation statements)
references
References 67 publications
4
104
0
Order By: Relevance
“…Researches has demonstrated that IFIT1 can restrict HCV growth by inhibiting HCV replication, and the expression level of IFIT1 can be potential biomarker of response to IFNα in patients with HCV[29,38]. IFIT1 restricts the translation and replication of many other viruses such as HPV, HIV and alphavirus, and promotes the induction of IFNα to enhance immune response[18,39,40]. All these evidences demonstrate the importance of IFIT1 in immune system and virus inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researches has demonstrated that IFIT1 can restrict HCV growth by inhibiting HCV replication, and the expression level of IFIT1 can be potential biomarker of response to IFNα in patients with HCV[29,38]. IFIT1 restricts the translation and replication of many other viruses such as HPV, HIV and alphavirus, and promotes the induction of IFNα to enhance immune response[18,39,40]. All these evidences demonstrate the importance of IFIT1 in immune system and virus inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that IFIT1 acts as an important innate immune bottleneck which shows positive regulation on downstream genes[17]. High level of type I IFN is observed in IFIT1-expressing cells[18]. Researches have indicated that the antiviral activity of IFIT1 is modulated by 2’-O methylation of viral RNA.…”
Section: Introductionmentioning
confidence: 99%
“…GFP also was included in the genome of all viruses to allow visualization of virus infection both in vitro and in vivo. Alphaviruses expressing recombinant proteins through a second subgenomic promoter have been well characterized and have been shown to be useful for tracking viral replication and spread (33,(44)(45)(46). RT-PCR and DNA sequencing of RT-PCR products confirmed that rescued viruses maintained their chimeric composition (data not shown).…”
Section: Chikv/sfv But Not Chikv/veev E2 Chimeras Can Be Rescued Andmentioning
confidence: 95%
“…During the host response to infection, secretion of IFN-β or IFN-α engages the type I IFN receptor complex activating the JAK/STAT signaling cascade leading to upregulation of antiviral interferon stimulation genes (ISGs) that inhibit alphavirus replication [2933]. Alphaviruses are known to suppress the induction of the innate immune response during infection through different mechanisms.…”
Section: Viral Antagonism Of the Innate Immune Responsementioning
confidence: 99%
“…The activity of the translation-inhibiting ISG, IFIT-1, is limited by the lack of free nucleotides in the 5’ NTR of VEEV and the presence of a rigid stem-loop structure. This prevents the recognition of the virus type 0 cap structure by IFIT-1 and inhibition of virus translation [31,33]. Mutations in the 5’ NTR secondary structure present in the attenuated TC-83 vaccine strain lead to IFIT-1 recognition of VEEV RNA and in vivo attenuation [31].…”
Section: Viral Antagonism Of the Innate Immune Responsementioning
confidence: 99%